Kick some glass : 10 ways women succeed at work on their own terms - Martineau, Jennifer; Mount, Portia (McGraw-Hill Education, 2019)
Empowering you to break through your glass ceiling, this no-nonsense guide leads you toward understanding your context and uncovering what you really want, what your definition of success is, what your values are, and how to set the goals to reach your potential. --